Obstructive sleep apnoea. (June 2020) - Turnbull, Chris; Zaki, Irfan; Hardinge, Maxine
Abstract: Obstructive sleep apnoea occurs during sleep when there is repeated pharyngeal collapse that obstructs the airway and causes repeated awakenings from sleep. Sufferers complain of unrefreshing sleep and daytime somnolence. Bed partners usually report snoring with apnoeic attacks. Problems with tasks requiring concentration, such as driving, are common. In severe sleep apnoea the rate of road traffic accidents secondary to sleepiness is high. A sleep study incorporating respiratory assessment, is required to confirm the diagnosis and severity before the decision is made to initiate continuous positive airway pressure treatment. Milder cases can respond to a jaw advancement device and weight loss.